Early Intervention of Didang Decoction on MLCK Signaling Pathways in Vascular Endothelial Cells of Type 2 Diabetic Rats - Shoujiao Ye; Zhenqiang Song; Jing Li; Chunshen Li; Juhong Yang; Bai Chang (International Journal of Endocrinology)
In the study, type 2 diabetic rat model was established using streptozotocin (STZ) combined with a high-fat diet, and the rats were divided into control and diabetic groups. Diabetic groups were further divided into nonintervening, simvastatin, Didang Decoction (DDD) early-phase intervening, DDD mid-phase intervening, and DDD late-phase intervening groups. The expression level of MLCK was detected using Western Blot analysis, and the levels of cyclic adenosine monophosphate (cAMP), protein kinase C (PKC), and protein kinase A (PKA) were examined using Real Time PCR. Under the electron microscope, the cells in the early-DDD-intervention group and the simvastatin group were significantly more continuous and compact than those in the diabetic group. Compared with the control group, the expression of cAMP-1 and PKA was decreased in all diabetic groups, whereas the expression of MLCK and PKC was increased in early- and mid-phase DDD-intervening groups (P<0.05); compared with the late-phase DDD-intervening group, the expression of cAMP-1 and PKA was higher, but the level of MLCK and PKC was lower in early-phase DDD-intervening group (P<0.05). In conclusion, the early use of DDD improves the permeability of vascular endothelial cells by regulating the MLCK signaling pathway.